Consensus statement on indications for anti-angiogenic therapy in the management of corneal diseases associated with neovascularisation: outcome of an expert roundtable. Issue 1 (28th June 2011) - Cursiefen, Claus; Colin, Joseph; Dana, Reza; Diaz-Llopis, Manuel; Faraj, Lana A; Garcia-Delpech, Salvador; Geerling, Gerd; Price, Francis W; Remeijer, Lies; Rouse, Barry T; Seitz, Berthold; Udaondo, Patricia; et al.
Abstract : The cornea is the clear window at the front of the eye and is the eye's main refractive medium. Its transparency is essential for vision. Corneal neovascularisation is a common clinical problem with serious consequences for vision; it can compromise corneal transparency and plays a major role in corneal graft rejection by breaching corneal immune privilege. In this review, we formulate a consensus on the unmet medical needs in the management of corneal neovascularisation and outline a framework for the clinical research that is needed to identify suitable agents to meet these needs.